Thermal characterization of recycled polymer for additive manufacturing applications. (1st December 2016) - Boparai, K.S.; Singh, R.; Fabbrocino, F.; Fraternali, F.
Abstract: This work is focused on the thermal characterization of Nylon 6 based nano-composite (NC) material. Initially, melt flow index (MFI) test confirms the qualification of this material, as an alternative material for the fabrication of FDM filament. The differential scanning calorimeter (DSC) and thermogravimetric analysis (TGA) measurements characterize the material by recording their phase and mass changes as a function of temperature. The DSC results confirmed the decrease of crystallinity with the inclusion of nano fillers but also realized that these filler particles act as a thermodynamic sink and improves its stability. The TGA analysis also demonstrated the increase in thermal stability and flame retardancy level of NC material. In addition to above scanning electron microscopy analysis visualized the dispersion of filler materials in Nylon 6 matrix.